Transforming Toy Kids Camera into E-CAM (English–Camera) As a Media to Teach Vocabulary for Lower Primary Students (RETAIN, 2016)
Transforming Toy Kids Camera into E-CAM (English–Camera) As a Media to Teach Vocabulary for Lower Primary Students Intan Rachmatillah English Department, Faculty of Languages and Arts, State University of Surabaya intanrachmatillah@mhs.unesa.ac.id Ahmad Munir English Department, Faculty of Languages and Arts, State University of Surabaya ahmadmunir@unesa.ac.id Abstrak Flash card is a set of cards which consist of pictures and words. In contrary, the vocabulary in the flash card is in isolation. The young learners are not supposed to be exposed by single word instead of the use of sentences. Thus, an innovative media will be developed. The concept of this media is adapted from flashcard concept but completed with the camera toy flashlight, and technology assist. Therefore, the research questions of this study are (1) how is the form of English-Camera prototype? (2) How are the accuracy of English-Camera contents material and the vocabulary material of lower primary students? (3) How is the operation of using English-Camera? This study used R & D model by Borg and Gall (2003) to develop kids toy to become English-Camera for the teaching vocabulary for lower primary students. After designing the preliminary form of the product, the draft of English-Camera was tested to the media and material expert. This test aimed to know whether the material and physical appearance of English-Camera was suitable for the lower primary students. In the preliminary field testing, the data were gained from observation checklist and interview to know whether the accuracy of English-Camera contents material and the vocabulary material of lower primary students.Besides the data got from the observation and interview in the field test, for the second field test, the data were collected from the interview also to the students and the teacher. The first interview which consisted of 5 questions was addressed to 10 students from 1st graders. The second interview which involved 12 students from 2nd graders. And the 3rd graders contained 5 questions was addressed to 10 students. The interview was aimed at knowing the students’ response toward the media. In addition, manual book also design create to make the users easy to operate English-Camera and make the users comprehend the English-Camera component. Key words: Camera Toy, Flash Card, Lower Primary students, Vocabulary, English-Camera Abstract Flash Card adalah sekumpulan kartu yang terdiri dari gambar and kata. Namun, Kosakata dalam flashcard terisolasi. Anak-anak seharusnya tidak diperkenankan untuk belajar koskata dalam bahasa inggris dengan menggunakan satu kata tapi lebih dianjurkan dalam bentuk kalimat. Sehingga sebuah media inovasi akan dikembangkan. Oleh karena itu, masalah dalam penelitian ini adalah (1) bagaimana bentuk dari E-CAM (English-Camera)? (2) Bagaimana keakurasian antara material yang ada pada E-Cam dengan materi kosakata pada siswa kelas rendah? (3) Bgaimana pengoperasian E-Cam? Dalam penelitian ini menggunakan metode desain R & D olehBorg and Galluntuk mengubah permainan anak menjadi permainan pendidikan bernama English-Camera yang digunakan untuk mengajar siswa kelas dasar pada SD. Setelah melakukan design awal, gambaran dari E-CAM akan diuji cobakan pada ahli media dan materi. Tes ini dilakukan untuk mengetahui apakah tampilan dan konten dari E-CAMsudah sesuai dengan anak sekolah dasar. Pada percobaan awal, data diperoleh dari pengamatan dalam kelas dan wawancara untuk mengetahui apakah konten material pada E-CAM sesuai dengan materi pembelajaran kosakata pada anak sekolah dasar. Selain data didapat dari pengamatan dan wawancara pada uji coba lapangan, di tahap kedua uji coba, data didapat dari wawancara pada siswa dan guru. Wawancara pertama terdiri dari 5 pertanyaan yang ditujukan kepada 10 siswa kelas satu, 12 siswa kelas dua, dan untuk kelas 3 ada 5 pertanyaan yang ditujukan pada 10 siswa. Wawancara dilakukan dengan tujuan untuk mengetahui respon siswa terhadap media ini. Selain itu, buku panduan manual juga dibuat untuk memudahkan pengguna dalam pengoperasian English-Camera dan membuat pengguna mengerti komponen-komponen yang terdapat pada English-Camera. Kata kunci: Kamera Anak, Flashcard, Siswa Kelas Rendah di Sekolah Dasar, Kosakata, Kamera Bahasa Inggris